A new subspecies of Conyza montigena (Compositae: Astereae) from Tanzania. Issue 1 (March 2016) - Beentje, Henk; Hemp, Andreas
Summary A new taxon ofConyza has been found on Mt Kilimanjaro:C. montigena S. Moore subsp.kilimanjarica . Its close relatives are from the Ruwenzori and Virunga Mountains on the border of Uganda, Congo and Rwanda. As these relatives are varieties ofC. montigena, the geographical separation has led us to describe the new taxon as a subspecies ofC. montigena, subsp.kilimanjarica Beentje & Hemp.